2020
DOI: 10.3390/w12030848
|View full text |Cite
|
Sign up to set email alerts
|

Land Cover and Water Quality Patterns in an Urban River: A Case Study of River Medlock, Greater Manchester, UK

Abstract: Urban river catchments face multiple water quality challenges that threaten the biodiversity of riverine habitats and the flow of ecosystem services. We examined two water quality challenges, runoff from increasingly impervious land covers and effluent from combined sewer overflows within a temperate zone river catchment in Greater Manchester, North-West UK. Sub-catchment areas of the River Medlock were delineated from digital elevation models using a Geographical Information System. By combining flow accumula… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 44 publications
0
10
0
Order By: Relevance
“…Nevertheless, this fact points to the need to search for new predictors, which could explain nutrients variability during growing season, and such additional variables could include macrophytes density, as well as soil properties metrics [42]. Moreover, from scaling (weighting) methods presented in the literature [47,98,99], the use of buffer zones and/or Euclidean distance scaling seems to be the optimal solution for modelling purposes in lowland landscapes. Flow accumulation scaling could be difficult to apply due to blind drainage, similar to slope scaling in terms of small differences in elevation and low steeper slopes.…”
Section: Implications For Water Quality Managementmentioning
confidence: 99%
See 1 more Smart Citation
“…Nevertheless, this fact points to the need to search for new predictors, which could explain nutrients variability during growing season, and such additional variables could include macrophytes density, as well as soil properties metrics [42]. Moreover, from scaling (weighting) methods presented in the literature [47,98,99], the use of buffer zones and/or Euclidean distance scaling seems to be the optimal solution for modelling purposes in lowland landscapes. Flow accumulation scaling could be difficult to apply due to blind drainage, similar to slope scaling in terms of small differences in elevation and low steeper slopes.…”
Section: Implications For Water Quality Managementmentioning
confidence: 99%
“…Most of the work in this area, however, concerned catchments of over a hundred square kilometers, including upland or highland relief and steeper slopes of the terrain, where high hydrological connectivity and intensive erosion result in increased ion migration [43][44][45]. Meanwhile, few studies used widely available land cover datasets [39], while in most cases land cover metrics were computed with the use of government or self-classification-based land cover maps [46,47], making the results not comparable at the European scale. Finally, the results and conclusions of such investigations were not consistent and the effects of particular land cover metrics on nutrients ranged from negative to even positive [48,49].…”
Section: Introductionmentioning
confidence: 99%
“…The upstream section of the river had higher counts of benthic invertebrates when compared to the lower sections of the river. The distribution of the functional feeding groups (FFGs) ( Tables 2 and 4) showed the dominance of the collector-filterers (40%), which suggested the role of discharge in transporting drift that served as food to the groups [1], indicating the absence of non-forest covers and increased urban cover [14], especially at the more urban sections of the river. Windsor et al [54] noted that contaminated rivers found in the highly urban sites of South Wales, U.K., were characterised by their reduced taxonomic and functional diversity and simplified food web structure.…”
Section: Discussionmentioning
confidence: 99%
“…However, increasing human population growth and the associated agricultural and urban demands put large amounts of pressure on freshwater resources in terms of both the quality and quantity needed to satisfy human needs [5][6][7][8][9][10][11][12]. These pressures on rivers modify and sometimes limit the biodiversity abundance, which consequently impacts on the ecosystem system services provided by these rivers [10,13,14]. The impact of point and non-point source pollution on rivers' biodiversity, richness and abundance have been widely studied [15][16][17][18][19].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation